Cruel and unusual punishment: an analysis of the U.S. government's post-9/11 torture policies and recommendations for the closure of Guantanamo Bay - Barclay, Daniel T., author; Todd, Meagan, advisor (Colorado State University. Libraries, 2026)
For many years, the United States, as a beacon of liberty and champion of hope, had upheld guidelines for the humane treatment of prisoners held in custody by the government. Laws against cruel and unusual punishment were eventually codified on the international level by the Geneva Conventions of 1949, protecting those individuals that did not participate in the fighting. Then came the attacks of September 11, 2001, the most devastating and vulnerable attack on the American mainland since the Civil War. The terrorist group al-Qaeda claimed responsibility for the attacks in New York, Pennsylvania, and Washington D.C., and in the coming days, the War on Terror officially began, and the traditional rules and conventions of war changed. A makeshift detainee camp was erected at the U.S. Navy's Guantanamo Bay (Gitmo) base in Cuba to detain and interrogate individuals believed to have ties to al-Qaeda or the Taliban. This is where the CIA brought in two U.S. Air Force psychologists, James Mitchell and Bruce Jessen to teach CIA and military interrogators how to use what the CIA termed "enhanced interrogation techniques" or EITs. These tactics were developed by Mitchell and Jessen, who had no prior intelligence gathering or interrogation experience based on the U.S. Army's Survival, Evasion, Resistance, and Escape (SERE) tactics. SERE tactics were taught to special forces operatives who might be captured by an enemy that might use harsh measures to get them to break under extreme interrogation. The same mindset was applied to these EIT's by Mitchell and Jessen, who thought that the terrorists they capture would be tough to break, and that EITs were the only way to get detained terrorists to talk about their involvement in the 9/11 attacks, as well as when and where the next one will be. The EIT's used by the CIA on detainees at Gitmo, and then later at the Abu Ghraib prison in Iraq amount to torture, and that did not produce any actionable intelligence from any of the detainees. While the U.S. government has acknowledged its wrongdoings, and those administration officials, and interrogators are no longer in public service, no one has ever been prosecuted for these crimes. Both Presidents Bush and Obama have stated that they want to close Guantanamo Bay, but neither one was able to do it. While it seems unlikely that President Trump will close it completely, organizations such as Amnesty International and Human Rights Watch have called for its closure. In addition many former military, national security experts, and former prisoners have also been becoming more vocal about its closure, as it had already served its purpose many years ago.
Keywords: torture; EIT (enhanced interrogation techniques); CIA; SERE (survival, evasion, resistance, escape); Guantanamo Bay (Gitmo); terrorist; Geneva Conventions; Abu Ghraib; U.S. government; interrogator; The Bush Administration; detainee; al-Qaeda